ANALISIS PENGAWASAN, TUNJANGAN KINERJA DAN KEHADIRAN DALAM MENINGKATKAN KINERJA PEGAWAI SELAMA PANDEMI COVID-19 - Sri Widayati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Covid-19 pandemic has caused many government agencies to implement work from home policies. The study was conducted to determine the implications of supervision, performance allowances, and attendance in improving employee performance during the implementation of work from home during the pandemic. The research subjects were employees who worked at the Batu City Environmental Service. The research employed a qualitative analysis (triangulation analysis). The results show that supervision, performance allowance and attendance have an important role and influence in improving employee performance. The existence of supervision from superiors tends to make employees work more total and maximally. Performance allowances make employees more enthusiastic and motivated at work. A more relaxed and flexible working from home atmosphere makes employee attendance rates better and guaranteed.